البعد السيميائي للنص الأدبي وأصول تحليله - صفر، أحمد حاجي (جامعة محمد بوضياف المسيلة - كلية الآداب واللغات, 2020)
منذ أن انفتح العالم على بعضه البعض، بالحرب كما بالسلم، انفتحت العلوم الإنسانية على بعضها وعلى العلوم الأخرى، وصار المنتج الأدبي ميدانا تجريبيا لكل النظريات. ومن فكرة الطاقات الإبداعية انطلقت أغلب المدارس الحديثة في تحليل النص بحثا عن خطط التأليف والتوليف التي تنتج معنى، هو محور الدراسات التأويلية، ومنها السيميائية. لم يعد طرح قضية النص والنصية في هذا الإطار من قبيل الترف الفكري أو التفلسف الأدبي، بل صار ضرورة ملحة، لا لأن مفهوم النص قد تغير وحسب، بل لأن الأدوات التحليلية والنظريات النقدية أعادت حساباتها في النظر إلى المنتج الأدبي ووضعته موضع المساءلة بدل وضعه موضع الاتهام والتعرية. ويحاول هذا المقال أن يبحث في مفهوم السيميائية النصية، وأن يقترح أنموذجا من القواعد للتحليل السيميائي للنصوص الأدبية عموما، وللنصوص الأدبية التقليدية خاصة والتي تحوي خصائص دلالية وأسلوبية، ليست سهلة التحصيل أحيانا.
Since the world has opened up upon itself, in war as in peace, the Humanities too have opened up to each other and to the other sciences, and the literary output has become an experimental arena for all theories. It is from the idea of the creative energies that most modern schools have launched in the textual analysis in search of plans of authoring and synthesis that produce meaning is the focus of interpretive studies, including semiotics. The question of the text and textuality is no longer an issue of intellectual luxury or literary philosophizing. It has become an urgent necessity, not only because the concept of the text has changed, but also because the analytical tools and critical theories have re- assessed the method of looking at the literary product and placed it in the position of interrogation, rather than putting it into the position of accusation and denuding. This article tries to give the principle rules of semiotic analysis of a literary text in general, and notably the traditional texts.
Keywords: الأدب العربي -- التحليل السيميائي -- النقد الأدبي